INNOVATIVE METHODS AS AN IMPORTANT PART OF LEARNING FOREIGN LANGUAGES - О. V. Ovadiuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article deals with the role of information technologies in learning foreign languages. The paper states the great importance of IT in the learning process as well as in the process of raising motivation among students to a higher level. It also describes different multimedia methods among which the outline of video lessons, role-playing game lessons, distance learning and project based learning have the leading role. The article also points out that due to the application of multimedia technologies the possibilities of modern methods of learning foreign language are considerably broadened and diversified. The content of lessons with the help of IT is enriched, the rate of realization is high, and a teacher gets the possibility to use educational time more effectively, to invent the original methods of teaching and increase the volume of educational material for students' mastering and usage. The article analyses various language activity categories with the help of different types of modern technologies and their positive effect on language learning efficiency. It also states that the application of multimedia materials and computer networks abbreviates time of studies by almost three times, and the level of memorizing through the simultaneous use of images, sound and text is 30-40 percent more. Due to the use of multimedia means, students perfect all aspects of language: phonetic, grammatical, lexical and communicative. This allows mastering language material, language skills and abilities more effective and quicker.